Method for assembling array structures of capillary-assisted gold nanoparticle films
Patent Information
- Application Number
- CN202310543662.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-15
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-05-15
AI Technical Summary
有一些自组装方法会在组装过程中引入额外的不需要的物质,例如液-液两相自组装、三项自组装需要引入表面活性剂,这将不可避免地影响稀土纳米晶体上转换发光的增强效果
[0028]本发明提供了一种基于毛细管辅助金纳米颗粒组装薄膜阵列结构的方法,具体方法如下:将APTES处理后的毛细管浸泡在金纳米颗粒胶体中;在浸泡完成后,取出毛细管,排空残留的金纳米颗粒胶体,并自然干燥,金纳米颗粒胶体会在静电力的作用下在毛细管内壁形成金纳米颗粒薄膜阵列结构。由于金纳米颗粒胶体表面由一层带负电的柠檬酸根包裹,而APTES处理后的毛细管内壁覆盖一层带正电的NH3+,在静电力的作用以及毛细管的虹吸作用下,分散在金纳米颗粒胶体中的金纳米颗粒会很容易被吸附在毛细管的内壁组装成金纳米颗粒薄膜阵列,因此在毛细管的辅助作用下该金纳米颗粒胶体组装成金纳米颗粒薄膜阵列结构,将预设稀土纳米晶体沉积在金纳米颗粒薄膜阵列结构的表面;并且由于金纳米颗粒薄膜阵列结构具有丰富的纳米间隙,在外界光场的激发下会形成许多密集的“热点”,在这些“热点”处分布有极强的局域电磁场,当稀土纳米晶体位于该金纳米颗粒薄膜阵列结构表面的这些“热点”区域时,稀土纳米晶体的上转换发光会由于局域表面等离激元模式共振产生的电磁场增强,以及发射光与金属纳米颗粒吸收峰相耦合产生的局域表面等离激元共振而增强,并且由于本发明的方法制备流程简单、快速、对环境要求低,制备过程中没有引入多余的物质,可用于稀土纳米晶体的上转换发光增强,在实际的光谱增强、防伪技术、生物成像等领域具有重要的潜在应用价值。
Smart Images

Figure CN116574499B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical enhancement structure fabrication, specifically to a method for assembling thin film array structures based on capillary-assisted gold nanoparticles. Background Technology
[0002] With the development of nanotechnology, the fabrication of surface plasmon substrates, which combine high repeatability, high reproducibility, high stability, high sensitivity, large area, low cost, and simple processes, is becoming increasingly promising. Therefore, through appropriate methods, morphology-controllable metallic nanostructure substrates can be fabricated, and the electromagnetic field enhancement generated by surface plasmon resonance can be utilized to achieve upconversion luminescence enhancement of rare-earth nanocrystals. Currently, surface plasmon enhancement has significant scientific research value and engineering application potential, and is gradually becoming one of the research hotspots of widespread interest among researchers.
[0003] In existing technologies, assembling metal nanoparticles into various morphologies using different self-assembly techniques is an important tool for studying surface plasmon coupling and its enhanced spectral effects. However, some self-assembly methods introduce unwanted substances during the assembly process; for example, liquid-liquid two-phase self-assembly and three-phase self-assembly require surfactants, which inevitably affect the enhancement of upconversion luminescence in rare-earth nanocrystals. The application presented here employs a simple and convenient preparation method that effectively avoids these problems.
[0004] However, since metal nanostructures of different shapes have different enhancement effects, there is an urgent need in the prior art for a structure or a method for preparing such a structure that can effectively enhance the upconversion luminescence of rare earth nanocrystals. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of the prior art by providing a method for assembling a thin film array structure based on capillary-assisted gold nanoparticles, thereby obtaining a structure or a method for preparing a structure that can effectively enhance the upconversion luminescence of rare earth nanocrystals.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] This invention provides a method for assembling thin film array structures based on capillary-assisted gold nanoparticles, the method comprising:
[0008] The capillaries were treated with APTES (3-aminopropyltriethoxysilane), and the treated capillaries were then immersed in a gold nanoparticle colloid.
[0009] After soaking, the capillary tube was removed, the residual gold nanoparticle colloid was drained, and it was allowed to dry naturally. The gold nanoparticles assembled into a gold nanoparticle thin film array structure on the inner wall of the capillary tube.
[0010] Pre-defined rare earth nanocrystals are deposited on the surface of the gold nanoparticle thin film array structure.
[0011] Optionally, the capillary can be treated with APTES as follows:
[0012] First, the inner and outer surfaces of the capillary are ultrasonically cleaned sequentially with acetone, ethanol, and deionized water.
[0013] After complete drying, the capillary is placed in an APTES solution, causing the APTES to undergo a hydrolysis reaction inside the capillary, forming positively charged amino groups on the inner wall of the capillary.
[0014] After APTES treatment, the inner and outer surfaces of the capillary are then ultrasonically cleaned with ethanol and deionized water in sequence.
[0015] Optionally, the capillary tube can be immersed in APTES solution for 12 hours at 30°C.
[0016] Optionally, the gold nanoparticle colloid used is obtained in the following manner:
[0017] A sodium citrate solution was prepared by dissolving sodium citrate crystals in deionized water.
[0018] Chloroauric acid solution was prepared by dissolving chloroauric acid tetrahydrate crystals in deionized water.
[0019] Add the predetermined volume of chloroauric acid solution to the deionized aqueous solution and heat and stir.
[0020] A predetermined amount of sodium citrate solution was added to a deionized aqueous solution containing chloroauric acid solution, and the mixture was heated and stirred. After the reaction was complete, the mixture was cooled to room temperature to obtain gold nanoparticle colloids.
[0021] Optionally, the concentration of the prepared sodium citrate solution is 0.035 mol / L;
[0022] The concentration of the chloroauric acid solution is 0.01 mol / L;
[0023] During heating and stirring, a magnetic heating stirrer was used for water bath heating. The temperature of the magnetic heating stirrer was set to 110℃. Sodium citrate solution was added to a deionized aqueous solution containing chloroauric acid solution and the reaction was carried out for 20 minutes.
[0024] Optionally, the capillary is immersed in the gold nanoparticle colloid at 3°C for 12 hours.
[0025] Optionally, the deposition of the preset rare earth nanocrystals on the surface of the gold nanoparticle thin film array structure is achieved by dissolving the preset rare earth nanocrystals in a PMMA (polymethyl methacrylate) solution and depositing the rare earth nanocrystals on the surface of the gold nanoparticle thin film array structure by deposition; wherein the solvent for PMMA can be anisole or dichloromethane.
[0026] Optionally, the preset rare earth nanocrystals are NaYF4:10%Yb 3+ / 2%Er 3+ Or any one of NaErF4 and NaYF4.
[0027] The beneficial effects of this invention are:
[0028] This invention provides a method for assembling a thin film array structure based on capillary-assisted gold nanoparticle assembly. The specific method is as follows: An APTES-treated capillary is immersed in a gold nanoparticle colloid. After immersion, the capillary is removed, the residual gold nanoparticle colloid is drained, and the capillary is allowed to dry naturally. Under the influence of electrostatic force, the gold nanoparticle colloid forms a gold nanoparticle thin film array structure on the inner wall of the capillary. This is because the surface of the gold nanoparticle colloid is coated with a layer of negatively charged citrate ions, while the inner wall of the APTES-treated capillary is covered with a layer of positively charged NH4+ ions. 3+ Under the influence of electrostatic force and capillary attraction, gold nanoparticles dispersed in a gold nanoparticle colloid are easily adsorbed onto the inner wall of the capillary and assembled into a gold nanoparticle thin film array. Therefore, with the assistance of the capillary, the gold nanoparticle colloid assembles into a gold nanoparticle thin film array structure, and pre-deposited rare earth nanocrystals are deposited on the surface of this structure. Furthermore, due to the abundant nano-intervals in the gold nanoparticle thin film array structure, many dense "hot spots" are formed under the excitation of an external light field. These "hot spots" are distributed with extremely strong local electromagnetic fields. When rare earth nanocrystals are deposited... When rare-earth nanocrystals are located in these "hot spot" regions on the surface of the gold nanoparticle thin film array structure, the upconversion luminescence of the rare-earth nanocrystals is enhanced by the electromagnetic field generated by the resonance of local surface plasmon modes and the local surface plasmon resonance generated by the coupling of the emitted light with the absorption peak of the metal nanoparticles. Furthermore, since the preparation method of this invention is simple, rapid, and has low environmental requirements, and does not introduce any extra substances during the preparation process, it can be used to enhance the upconversion luminescence of rare-earth nanocrystals, and has important potential application value in practical fields such as spectral enhancement, anti-counterfeiting technology, and bioimaging. Attached Figure Description
[0029] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 A flowchart illustrating a method for assembling a thin film array structure based on capillary-assisted gold nanoparticles, provided in an embodiment of the present invention;
[0031] Figure 2 This is a flowchart illustrating the preparation of gold nanoparticle colloids according to an embodiment of the present invention;
[0032] Figure 3 The enhanced spectra of a capillary-assisted assembled gold nanoparticle thin film array structure for different rare-earth nanocrystal systems are provided in this embodiment of the invention. M-RE1-1 represents NaYF4:10% Yb dissolved in anisole as PMMA solvent. 3+ / 2%Er 3+ M-RE1-2 represents NaYF4:10% Yb dissolved in dichloromethane as PMMA solvent. 3+ / 2%Er 3+ M-RE1-3 represents NaYF4:10%Yb dissolved in ethanol and naturally dried. 3+ / 2%Er 3+ M-RE2 represents NaErF4@NaYF4 dissolved in PMMA solvent with anisole, and those without the M designation are blank control groups not placed on the gold nanoparticle array;
[0033] Figure 4 The image shows a comparison of the enhancement factor of red and green light of rare earth nanocrystals in different systems and the red-green ratio before and after enhancement for a capillary-assisted assembled gold nanoparticle thin film array structure provided in this embodiment of the invention.
[0034] Figure 5 The graph shows the dependence of rare-earth nanocrystal upconversion emission intensity on excitation power and the variation of red-green ratio of the upconversion emission spectrum with excitation power for a capillary-assisted assembled gold nanoparticle thin film array structure provided in this embodiment of the invention.
[0035] Figure 6 The rare earth nanocrystals NaYF4:10%Yb in this embodiment of the invention are 3+ / 2%Er 3+ @NaYF4, NaYF4 assembled with capillary assistance: 10% Yb 3+ / 2%Er 3+@NaYF4 and NaYF4:10%Yb on a capillary-assisted assembled gold nanoparticle thin film array structure 3+ / 2%Er 3+ @NaYF4 red and green upconversion luminescence lifetime decay curves. Detailed Implementation
[0036] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are one embodiment of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0037] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0038] To make the implementation process of this invention clearer, a detailed description will be provided below in conjunction with the accompanying drawings.
[0039] Figure 1 A flowchart illustrating a method for assembling thin film array structures based on capillary-assisted gold nanoparticles, as provided in this embodiment of the invention; Figure 1 As shown, this invention provides a method for assembling thin film array structures based on capillary-assisted gold nanoparticles. For ease of understanding, the method for assembling thin film array structures based on capillary-assisted gold nanoparticles is described in detail below. For simplicity, this method is referred to simply as the "method," which includes:
[0040] S101. The capillary is treated with APTES, and the treated capillary is immersed in gold nanoparticle colloid.
[0041] The capillary tubes are treated with APTES as follows:
[0042] First, the inner and outer surfaces of the capillary are ultrasonically cleaned sequentially with acetone, ethanol, and deionized water.
[0043] After complete drying, the capillary is placed in an APTES solution, causing the APTES to undergo a hydrolysis reaction inside the capillary, forming positively charged amino groups on the inner wall of the capillary.
[0044] After APTES treatment, the inner and outer surfaces of the capillary are then ultrasonically cleaned with ethanol and deionized water in sequence.
[0045] In this embodiment of the invention, after the capillary is cleaned and dried, it is placed in an APTES solution. Due to the capillary's suction effect, APTES can treat the inner and outer surfaces of the capillary. Because APTES undergoes a hydrolysis reaction inside the capillary, a layer of positively charged NH4+ will coat the inner wall of the capillary. 3+ This is for subsequent processing. The conditions for APTES treatment, in which the capillary is placed in the APTES solution, are: 30°C, 12 hours.
[0046] The capillary tube of the present invention is used to carry the structure to be prepared in the present invention. The size of the capillary tube should be able to accommodate a predetermined volume of gold nanoparticle colloid. No specific limitation is made here. For clarity, the inner diameter of the capillary tube is 0.3 mm.
[0047] During capillary cleaning, the capillary is ultrasonically cleaned in acetone, and its inner and outer surfaces are rinsed using fluidity to remove organic impurities. Since acetone is soluble in ethanol, the capillary after acetone ultrasonic cleaning is placed in an ultrasonic cleaning device filled with ethanol, and its inner and outer surfaces are rinsed using fluidity to remove acetone and other impurities. Because ethanol and water are miscible in any proportion, the capillary after ethanol cleaning is placed in an ultrasonic cleaning device filled with deionized water, and its inner and outer surfaces are rinsed using fluidity. Finally, it is dried in a clean oven until ready for use.
[0048] S102. After soaking, remove the capillary tube, drain the remaining gold nanoparticle colloid, and allow it to dry naturally. The gold nanoparticles assemble into a gold nanoparticle thin film array structure on the inner wall of the capillary tube.
[0049] In this embodiment of the invention, the capillary is immersed in the gold nanoparticle colloid at 3°C for 12 hours. To obtain a uniform morphology, the immersion time should not be too long or too short. Due to the capillary's suction effect, the gold nanoparticle colloid easily enters the capillary. Furthermore, the gold nanoparticles used in this step are synthesized using a wet chemical method, and typically carry a negative charge (i.e., negatively charged citrate ions) due to a protective agent on their surface. The inner wall of the capillary treated with APTES is coated with a layer of positively charged NH4+. 3+ With the aid of capillary action, gold nanoparticles can easily enter the capillary; and due to electrostatic interaction, the gold nanoparticles coated with negatively charged citrate ions can interact with a layer of positively charged NH4+ ions covering the inner wall of the capillary. 3+Combined, under the combined action of capillary action and electrostatic force, gold nanoparticles can easily assemble into a gold nanoparticle thin film array on the inner wall of the capillary, thereby obtaining the gold nanoparticle assembled thin film array structure substrate of the present invention.
[0050] S103. Preset rare earth nanocrystals are deposited on the surface of the gold nanoparticle assembled thin film array structure.
[0051] A predetermined rare-earth nanocrystal is dissolved in a prepared PMMA solution, and the PMMA-dissolved rare-earth nanocrystal is uniformly deposited onto the surface of the gold nanoparticle thin film array structure by deposition; wherein the solvent for PMMA can be anisole or dichloromethane. Optionally, the predetermined rare-earth nanocrystal is NaYF4:10%Yb 3+ / 1%Er 3+ The rare-earth nanocrystals can be either NaErF4 or NaYF4. Under excitation by an external light field (980nm laser), the incident and emitted light fields of the upconversion luminescence process of the rare-earth nanocrystals adsorbed on the surface of the gold nanoparticle thin film array structure are enhanced due to resonance with the local surface plasmon modes, thus achieving enhanced upconversion luminescence. A PMMA thin film of the rare-earth nanocrystals is deposited on the surface of the gold nanoparticle thin film array structure, thus providing a rare-earth nanocrystal PMMA thin film layer on the surface of the gold nanoparticle thin film array structure on the preset substrate.
[0052] Figure 2 This is a flowchart illustrating the preparation process of gold nanoparticle colloids according to an embodiment of the present invention; as shown below. Figure 2 As shown, optionally, the gold nanoparticle colloid in this embodiment of the invention is obtained in the following manner:
[0053] S201. Dissolve sodium citrate crystals in deionized water to prepare a sodium citrate solution.
[0054] Sodium citrate crystals were dissolved in a pre-designed container containing deionized water, and the container was heated and stirred to obtain a sodium citrate solution. In this embodiment, the concentration of the prepared sodium citrate solution was 0.035 mol / L. The following description uses one part each of sodium citrate crystals and deionized water, where one part contains 0.08 g of sodium citrate crystals and one part contains 8 mL of deionized water. Specifically, 0.08 g of sodium citrate (Na3C6H5O7·2H2O) crystals were dissolved in 8 mL of deionized water to prepare a 0.035 mol / L sodium citrate solution.
[0055] S202. Chloroauric acid solution is prepared by dissolving chloroauric acid tetrahydrate crystals in deionized water.
[0056] Chloroauric acid tetrahydrate crystals are dissolved in a pre-set container containing deionized water. The container is stirred and heated to accelerate the melting of the chloroauric acid tetrahydrate crystals, resulting in a chloroauric acid solution in the container. In this embodiment, the concentration of the chloroauric acid solution is 0.01 mol / L. The chloroauric acid tetrahydrate crystals and deionized water are described separately, with one portion of chloroauric acid tetrahydrate crystals being 0.036 g and the other portion of deionized water being 10 mL. Specifically, 0.036 g of chloroauric acid tetrahydrate (HAuCl4·4H2O) crystals are dissolved in 10 mL of deionized water to prepare a 0.01 mol / L chloroauric acid solution.
[0057] S203. Add the pre-prepared chloroauric acid solution to the deionized water solution and heat and stir.
[0058] First, deionized water is poured into an Erlenmeyer flask and heated in a water bath while stirring. To ensure sufficient heating, in this embodiment, the temperature of the magnetic stirrer is set to 110°C. Specifically, the liquid phase in this step is an aqueous environment. Unless otherwise specified, all solutions are aqueous solutions, and all water used is deionized water (resistivity greater than 18 MΩ). To ensure the reaction proceeds under suitable conditions, the volume of deionized water should be appropriately set; no specific limit is made here, but for clarity, 77.5 mL is used. The reaction temperature is maintained by water bath heating to ensure the reaction proceeds normally. Since the boiling point of water is 100°C under standard atmospheric pressure, the temperature of the magnetic stirrer should be set no lower than 100°C to ensure continuous boiling of the water in the water bath. Then, a pre-set chloroauric acid solution is added to the deionized aqueous solution and heated while stirring. In this step, sodium citrate needs to reduce gold ions to form gold nanoparticles.
[0059] S204. Add the predetermined amount of sodium citrate solution to the deionized aqueous solution containing chloroauric acid solution, heat and stir, and cool to room temperature after the reaction is complete to obtain gold nanoparticle colloid.
[0060] The pre-prepared sodium citrate solution was poured into an Erlenmeyer flask and heated with stirring. After the reaction was complete, it was cooled to room temperature to obtain gold nanoparticle colloids. Specifically, sodium citrate was used as a reducing agent, while citrate ions also acted as a protecting agent to prevent the gold nanoparticles from agglomerating. It should be noted that, to ensure a complete reaction without damaging the morphology and dispersibility of the synthesized gold nanoparticles, the reaction time should not be too short or too long, and should be determined according to the specific conditions such as the concentration of reactants and the reaction environment. In this embodiment, the sodium citrate solution was added to a deionized aqueous solution containing chloroauric acid solution and the reaction was carried out with heating and stirring for 20 minutes. The amount of sodium citrate solution used was calculated based on the chemical formula and is not specifically limited here. To ensure a complete reaction, one or more reactants are usually set in excess. Therefore, after this step, centrifugation with deionized water is required to remove excess reagents. To ensure thorough washing without damaging the citrate ion protecting agent on the surface of the gold nanoparticles, the number of centrifugation cycles should not be too many or too few, and can be determined according to the specific situation. It is not specifically limited here, but for clarity, three centrifugation cycles are used here.
[0061] To further illustrate the upconversion luminescence enhancement effect of the pre-designed rare-earth nanocrystals, the method of this invention utilizes capillary-assisted assembly of gold nanoparticles to obtain a large-area, monolayer, dense gold nanoparticle thin film array structure. This structure contains numerous nanoscale gaps, which, under the excitation of incident light, form many electromagnetic "hot spots," thereby significantly enhancing the upconversion luminescence of the rare-earth nanocrystals in the near-field region.
[0062] Figure 3 The image shows the enhanced spectrum of rare-earth nanocrystals achieved by a capillary-assisted assembled gold nanoparticle thin film array structure, as provided in an embodiment of the present invention. Figure 3 As shown, anisole ( Figure 3 a) and dichloromethane ( Figure 3 b) The rare earth nanocrystals were dissolved using PMMA as a solvent and deposited onto the surface of a gold nanoparticle thin film array structure. A comparison was made using a method where the rare earth nanocrystals were naturally dried onto the surface of the gold nanoparticle thin film array structure. Figure 3 As shown in c, the rare earth nanocrystals used are NaYF4:10%Yb 3+ / 2%Er 3+Comparative studies revealed that natural drying did not significantly enhance the upconversion luminescence of rare-earth nanocrystals; however, the enhancement effect was most pronounced using anisole as a solvent, followed by dichloromethane. Taking green light as an example, the enhancement factors for the three methods were 2.56, 1.86, and 1.12, respectively. This result was found to be related to the drying rate of the solvent. Compared to natural drying and dichloromethane, anisole had the slowest drying rate, which facilitated the formation of a uniform rare-earth nanocrystal layer on the surface of the gold nanoparticle thin film array structure, preventing aggregation and thus resulting in a higher enhancement effect. Finally, another rare-earth nanocrystal, NaErF4@NaYF4, was used for enhancement on the substrate. Similarly, it was found to enhance upconversion luminescence by 1.97 times, demonstrating that the prepared substrate had a good enhancement effect.
[0063] Figure 4 The image shows the enhancement factor of red and green light from rare earth nanocrystals by a capillary-assisted assembled gold nanoparticle thin film array structure provided in this embodiment of the invention, as well as a comparison of the red-green ratio before and after enhancement. Figure 4 The study showcased the green and red peak area ratios of different system architectures. For different systems, the results indicated that the NaYF4:10%Yb... 3+ / 2%Er 3+ The enhancement effect on green light emission is significantly better than that on red light emission. For another rare-earth nanocrystal, NaErF4@NaYF4, the enhancement effect on red light emission is significantly better than that on green light emission. Similarly, looking at the red-to-green ratio results, for the M-RE1-1 and M-RE1-2 systems, the red-to-green ratio decreased significantly after enhancement, indicating that the system using anisole and dichloromethane as PMMA solvents for dissolution of rare-earth nanocrystals enhances green light emission better than red light emission. Conversely, for the M-RE2 system, the red-to-green ratio increased significantly after enhancement, proving that the M-RE2 system enhances red light emission significantly better than green light emission. This demonstrates that by selecting different rare-earth nanocrystals (in this invention, NaYF4:10%Yb...), the enhancement effect can be improved. 3+ / 2%Er 3+ Taking NaErF4@NaYF4 as an example, the capillary-assisted assembly of gold nanoparticle thin film array structure provided by this invention can effectively control the emission enhancement of red and green light, thereby controlling different red-green ratios and enabling wider applications.
[0064] Figure 5This invention provides an embodiment of a capillary-assisted assembled gold nanoparticle thin film array structure, illustrating the dependence of upconversion emission intensity on excitation power of rare-earth nanocrystals, and the variation of the red-green ratio of the upconversion emission spectrum with its excitation power. To further demonstrate the role of excitation enhancement in the upconversion luminescence enhancement process, the study investigated rare-earth nanocrystals NaYF4:10%Yb dissolved in anisole under laser excitation. 3+ / 2%Er 3+ The power dependence of the architecture, with excitation power ranging from 120mW to 240mW, such as Figure 5 As shown in a, with increasing excitation power, more E values are in the ground state. r3+ The excitation of ions leads to the release of more photons, resulting in a significant increase in overall emission intensity. This indicates that while the luminescence intensity increases with increasing power, the enhancement effect gradually weakens. This is because at lower power levels, most Er... 3+ All ions were in the ground state. With increasing power, the luminescence intensity changed significantly. As more ions gradually transitioned to the excited state, the results showed that with increasing pump power, the intensity increased compared to the ground state. Figure 5 b and Figure 5 c. It was found that in the pump power test, as the laser power gradually increased, the capillary-assisted assembly of the gold nanoparticle thin film array structure was less effective for rare earth nanocrystals NaYF4:10%Yb. 3+ / 2%Er 3+ The enhancement of green light in the system was significantly greater than that of red light; from Figure 5 It is evident from the red-green ratio and the emission intensity of red and green light that the red-green ratio shows a decreasing trend, and the enhancement factor of red light is slightly lower than that of green light. The results indicate that in the pump power test, simulating excitation enhancement by varying the power leads to enhanced interaction between the excitation light and the local electromagnetic field on the surface of the capillary-assisted assembled gold nanoparticle thin film array structure, thereby increasing the upconversion luminescence intensity of the rare-earth nanocrystals. The difference in the red-green ratio also suggests that emission enhancement contributes to the upconversion luminescence enhancement.
[0065] Figure 6 The rare earth nanocrystals NaYF4:10%Yb in this embodiment of the invention are 3+ / 2%Er 3+ @NaYF4, NaYF4 assembled with capillary assistance: 10% Yb 3+ / 2%Er 3+ @NaYF4 and NaYF4:10%Yb on a capillary-assisted assembled gold nanoparticle thin film array structure 3+ / 2%Er 3+ @NaYF4 upconversion luminescence lifetime decay curve. Figure 6a is the upconversion luminescence lifetime curve of green light (540nm) obtained under an excitation light of 980nm. The upconversion luminescence lifetimes of the three curves were calculated to be 208.55, 442.85, and 609.59μs, respectively, through fitting. Figure 6 b represents the upconversion luminescence lifetime curves for red light (654 nm) obtained under an excitation light of 980 nm. The corresponding upconversion luminescence lifetimes for the three wavelengths under red light emission are 344.2, 617.07, and 628.17 μs, respectively. The figure shows that the rate of increase in luminescence lifetime decreased after the introduction of the capillary substrate, mainly due to the introduction of a PMMA film as an isolation layer. The addition of the isolation layer led to a sharp reduction in the quenching effect, thus decreasing the rate of increase in luminescence lifetime and extending the luminescence lifetime of the system after the addition of the PMMA film. In the experiment, the NaYF4:10%Yb gold nanoparticle thin film array structure was assembled using capillary assistance. 3+ / 2%Er 3+ Compared to rare-earth nanocrystals whose green upconversion luminescence lifetime was unaffected by the gold nanoparticle thin film array structure, the green upconversion luminescence lifetime of @NaYF4 was significantly prolonged. This indicates that the emission enhancement resulting from the coupling of the green light emitted by the rare-earth nanocrystals with the absorbed light from the gold nanoparticles plays a role in enhancing upconversion luminescence. In the experiment, since capillary-assisted assembled gold nanoparticle thin film array structures were used, the variation law of green light emission lifetime was approximately the same as that of red light emission lifetime under similar coupling effects.
[0066] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for assembling thin film array structures based on capillary-assisted gold nanoparticles, characterized in that, The method includes: A sodium citrate solution was prepared by dissolving sodium citrate crystals in deionized water. Chloroauric acid solution was prepared by dissolving chloroauric acid tetrahydrate crystals in deionized water. Add the predetermined volume of chloroauric acid solution to the deionized aqueous solution and heat and stir. A predetermined amount of sodium citrate solution was added to a deionized aqueous solution containing chloroauric acid solution, and the mixture was heated and stirred. After the reaction was complete, the mixture was cooled to room temperature to obtain gold nanoparticle colloids. The concentration of the prepared sodium citrate solution was 0.035 mol / L; The concentration of the chloroauric acid solution is 0.01 mol / L; During heating and stirring, a magnetic heating stirrer was used for water bath heating. The temperature of the magnetic heating stirrer was set to 110 ℃. Sodium citrate solution was added to a deionized aqueous solution containing chloroauric acid solution and the reaction was carried out for 20 min. The capillaries were treated with APTES, and the treated capillaries were then immersed in gold nanoparticle colloid at 3°C for 12 hours. After soaking, the capillary tube was removed, the residual gold nanoparticle colloid was drained, and it was allowed to dry naturally. The gold nanoparticles assembled into a gold nanoparticle thin film array structure on the inner wall of the capillary tube. The method for depositing the pre-set rare earth nanocrystals on the surface of the gold nanoparticle thin film array structure involves dissolving the pre-set rare earth nanocrystals in a PMMA solution and then depositing them onto the surface of the gold nanoparticle thin film array structure using a deposition method. The PMMA solution is selected as a solvent for anisole or dichloromethane, and the pre-set rare earth nanocrystals are NaYF4:10%Yb. 3+ / 2%Er 3+ Or NaErF4@NaYF4.
2. The method for assembling a thin film array structure based on capillary-assisted gold nanoparticles according to claim 1, characterized in that, The method of treating capillaries with APTES is as follows: First, the inner and outer surfaces of the capillary are ultrasonically cleaned sequentially with acetone, ethanol, and deionized water. After complete drying, the capillary is placed in an APTES solution for treatment. APTES undergoes a hydrolysis reaction inside the capillary, forming a positively charged amino layer on the inner wall of the capillary. After APTES treatment, the inner and outer surfaces of the capillary are then ultrasonically cleaned with ethanol and deionized water in sequence.
3. The method for assembling thin film array structures based on capillary-assisted gold nanoparticles according to claim 2, characterized in that, The capillary tube was immersed in APTES solution for 12 hours at 30 °C.